1983
DOI: 10.14430/arctic2261
|View full text |Cite
|
Sign up to set email alerts
|

Waterfowl Kill by Cree Hunters of the Hudson Bay Lowland, Ontario

Abstract: From 1974 to 1976 annual interviews were conducted with 9756 of male Indian potential hunters at James Bay and Hudson Bay coastal villages to determine waterfowl kill. Sample interviews were conducted at inland villages. Of those interviewed at coastal communities, 87% hunted waterfowl. The mean yearly take of all species ranged from 55 to 145 birds per hunter. Lesser Snow Geese and large Canada Geese were the main prey, averaging 38 350 and 23 152 birds shot per year, respectively. Small numbers of other goos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
1
17
1
Order By: Relevance
“…Whereas other studies demonstrated reduced harvests in years of early, rapid springs (Hanson and Currie, 1957;Prevett et al, 1983), harvests in this area were greater in earlier springs or their size appeared unrelated to spring phenology. Unlike more southerly harvests, Western Arctic harvests occurred at or near the terminus of spring migration.…”
Section: Factors Affecting the Harvestcontrasting
confidence: 80%
See 3 more Smart Citations
“…Whereas other studies demonstrated reduced harvests in years of early, rapid springs (Hanson and Currie, 1957;Prevett et al, 1983), harvests in this area were greater in earlier springs or their size appeared unrelated to spring phenology. Unlike more southerly harvests, Western Arctic harvests occurred at or near the terminus of spring migration.…”
Section: Factors Affecting the Harvestcontrasting
confidence: 80%
“…On a per hunter basis, average numbers harvested were similar to those of Cree hunters in the Hudson Bay Lowlands of Ontario (Prevett et al, 1983). Capabilities for handling and storing harvests and need likely contribute to limiting the overall take.…”
Section: Factors Affecting the Harvestmentioning
confidence: 76%
See 2 more Smart Citations
“…There are a few more studies that might be referred to, but one has to remember that this is an overview and its particular strength is in wetland classification. Those seeking a little more in the area of biodiversity may refer to Desroches et al (2010), James et al (1983), Peck (1972), Prevett & Lumsden (1983), and Sutherland et al (2005). Biological information has been gathered from the more accessible parts of the lowlands around Moosonee and at Churchill, Manitoba, and this can be searched online.…”
mentioning
confidence: 99%